Exogenous Melatonin Improves the Tibial Performance, Morphology and Metabolism Balance in Rapid Bone Growth Phase of Long Photoperiod Broilers - Miao Yu; Mengjie Xu; Guangju Wang; Jinghai Feng; Minhong Zhang (Agriculture, 2025)
Bone metabolism dynamic balance is pivotal to bone formation in broilers. Long photoperiods have resulted in leg bones disorders in broilers. Melatonin (MT) is an essential hormone that protects the growth and development of bones, but the functions of melatonin on leg bone metabolism are poorly defined in long photoperiod broilers. A total of 216 healthy 5-day-old Arbor Acres (AA) male broiler chickens were randomly allocated into three treatment groups, i.e., 12L:12D photoperiod, 18L:6D photoperiod, 18L:6D photoperiod with exogenous MT supplementation (18L:6D + MT) for 2 weeks. Here, we found that 18L:6D photoperiod increased tibial length (p < 0.001), circumference (p = 0.012) and long diameter (p = 0.003) of broilers, but decreased the tibial weight index (p = 0.038) and strength. The 18L:6D photoperiod induced the tibial cartilage damage, decreased the osteoblast/osteoclast ratio (p = 0.002) and decreased the medullary cavity collagen fiber (p = 0.018) in broilers. Exogenous MT improved the tibial strength, relieved the tibial cartilage damage, increased the tibia osteoblast activity, alleviated osteoclast recruitment and activation and enhanced the collagen fiber in medullary cavity in long photoperiod broilers. Taken together, exogenous MT improved the tibial performance, morphology and formation of broilers underlying long photoperiod.